2020
DOI: 10.31557/apjcp.2020.21.3.599
|View full text |Cite
|
Sign up to set email alerts
|

The Possible Role of Adipokines in HCV Associated Hepatocellular Carcinoma

Abstract: Background: Adipokines play an important role in the regulation of inflammation and tumor progression. Aim: Assessment of the possible role of adiponectin, leptin and visfatin in HCV associated hepatocellular carcinoma (HCC). Methods: patients were classified into 85 patients with HCV associated HCC, 100 patients with chronic hepatitis C viral (HCV) infection compared to 50 normal control (NC) subjects. All subjects included in the study were assessed for HCV infection by seropositive HCV antibodies, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 48 publications
1
5
1
Order By: Relevance
“…We found that serum visfatin and vaspin levels were substantially higher in cirrhotic patients with HCC than those with liver cirrhosis and healthy controls. This is consistent with earlier studies that found significantly higher serum levels of visfatin [ 11 , 12 , 19 ] and vaspin [ 6 , 18 ] in HCC patients, and this could be linked to more advanced inflammation and higher HCC risk [ 2 ]. Ninomiya et al .…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We found that serum visfatin and vaspin levels were substantially higher in cirrhotic patients with HCC than those with liver cirrhosis and healthy controls. This is consistent with earlier studies that found significantly higher serum levels of visfatin [ 11 , 12 , 19 ] and vaspin [ 6 , 18 ] in HCC patients, and this could be linked to more advanced inflammation and higher HCC risk [ 2 ]. Ninomiya et al .…”
Section: Discussionsupporting
confidence: 93%
“…To date, few studies have been conducted to investigate the role of serum visfatin and vaspin in HCC patients with inconclusive results. Moreover, their relevance in the diagnosis of HCC is not fully elucidated [ 2 , 6 , 11 , 12 ]. Therefore, this study aimed to assess the potential role of serum visfatin and vaspin in HCV-cirrhotic patients with and without HCC on top and their possible association with tumour characteristics and liver dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with different stages of HCV infection, the plasma visfatin level was associated with the presence of HCC [108]. Consistent with this finding, the serum levels of visfatin differed significantly among HCC, HCV, and normal control groups, and the visfatin level was associated with liver cirrhosis in HCV-infected patients [109]. On the other hand, no correlation between visfatin and HCV genotype, viral load, or treatment response to IFN-based therapy has been shown [107].…”
Section: Visfatinmentioning
confidence: 59%
“…Adiponectin, leptin, and visfatin have been found to be associated with liver cirrhosis in HCV-infected patients [109]. Sex was associated with leptin and adiponectin levels, and body mass index (BMI) was associated with leptin and PAI-1 levels in HCV-infected patients at baseline.…”
Section: Multiple Adipokinesmentioning
confidence: 99%
“…Also, LEP stimulates pathophysiological conditions, such as hematopoiesis and polycystic ovarian syndrome. Despite the relationship of LEP to people with obesity, the changes of LEP and LEPRs might be related to the risk of many types of cancer (Wang et al, 2004, Swellam and Hamdy, 2012, El-Daly et al, 2020.…”
Section: Research Articlementioning
confidence: 99%